1st international anatomy cadaveric workshop: from Korea to Sungai Buloh - Ker Woon, Choy; Adib Ridzuan, Nurul Raudzah (Faculty of Medicine, 2023)
Annyeong-haseyo!!! It's not an anatomy term, but it means "Hello" in Korean. The Department of Anatomy is excited to share our recent success of the "1st International Anatomy Cadaveric Workshop 2023" on 24th to 25th August 2023 at the Anatomy Dissection Hall of the Faculty of Medicine, UiTM.